Urine Sediment Profile Among Tailors at Pasar Minggu, Bengkulu City - Weni Pratiwi; Sahidan Sahidan; Halimatussa'diah Halimatussa'diah (Jurnal Fatmawati Laboratory & Medical Science, 2026)
Background: Tailoring is an occupation performed individually. During work activities, workers are at risk of occupational diseases and injuries due to inappropriate sitting positions, prolonged static muscle activity, and poor ergonomic posture. Activities involving forward bending, improper lifting techniques, and sitting for long periods may cause pain in body parts, joints, muscles, and the back. Long hours of static, seated occupational posture often leads to urinary stasis and decreased fluid intake. Objective: To describe microscopic urine sediment findings among tailors working in Pasar Minggu, Bengkulu City. Methods: This study used a descriptive design. Data collection was conducted through direct field surveys and urine sediment examinations with purposive sampling. This study occurred in 2025. Urine sediment is examined by manual microscopic examination. The population consisted of 18 tailors at Pasar Minggu, Bengkulu City. Results: Normal erythrocyte counts were found in 10 respondents (55.5%), while abnormal erythrocyte counts were found in 8 respondents (44.4%). Normal leukocyte counts were found in 15 respondents (83.3%), while abnormal leukocyte counts were found in 3 respondents (16.6%). Negative urine crystals were found in 15 respondents (83.3%), while positive crystals were found in 3 respondents (16.6%), consisting of calcium oxalate crystals. Conclusion: the detection of positive calcium oxalate crystals in 16.6% of respondents underscores a clinical predisposition to urolithiasis (kidney stones), highlighting the urgent need for hydration and posture interventions in this workspace among tailors at Pasar Minggu, Bengkulu City